Perilaku Konsumen Penggunaan E-Commerce Terhadap UMKM: (Studi Kasus UMKM di Daerah Balai Pustaka) - Rutinaias Haholongan; Rahel Alexcandra; Nina Allyassa; Elza Olivia; Rizaldi Ariana Zaputri (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Sate Padang which is a food that is no longer foreign to Indonesia, many people like satay in Padang, although some people do not like Padang satay and choose another type, therefore the target consumer of this MSME. Padang satay business People who love spicy and sweet food like meat and people who don't have a view on Padang satay food. In general, Padang satay is only marketed traditionally, therefore the application of new technology that makes it easier for sellers to market their products is very important. E-Commerce is widely known as a marketplace for Indonesia, which provides free shipping and low prices. E-Commerce comes with new services such as Shopee, Tokopedia and others, which offer online food delivery orders, of course the presence of E-Commerce can be a new option for choosing culinary delights in Indonesia, one of which is Sate Padang. Apart from being a forum for MSMEs to carry out business activities, it can also be used to maximize income.